(untitled) (The Dhaka University Journal of Earth and Environmental Sciences, 2021)
Tropical cyclone causes enormous damage of property and life in the coastal regions of Bangladesh. Majority of the damage during tropical cyclone occurs because of storm surge. Bangladesh is vulnerable to storm surge flooding due to its complex geometry and location. The huge loss of property and life can be reduced by predicting storm surge during a tropical cyclone. So, an attempt has been made in this study to see the effectiveness of predicting storm surge by Meteorological Research Institute (MRI) storm surge model from Japan Meteorological Agency (JMA). In this study, MRI storm surge model is used to simulate storm surge of five cyclones cyclone Bulbul (November 2019), cyclone Fani (May 2019), cyclone Mora (May 2017), cyclone Roanu (May 2016) and cyclone Komen (July 2015) were simulated using MRI storm surge model to see the effectiveness of the model. The model was run for 48-hours for two different data sets which are, European Centre for Medium-Range Weather Forecasts (ECMWF) data and Global Spectral Model (GSM) data. Simulated storm surge heights found from the model are compared with the reported surge height from Bangladesh Inland Water Transport Authority (BIWTA) and Bangladesh Meteorological Department (BMD). The model is able to simulate storm surge height, mean sea level pressure (MSLP) and wind data of all the selected cases. The time series graph developed using python comparing the simulated results of storm surge height data with observed data for the event cyclone Bulbul showed the simulated data of both NWP datasets were in line with the observed data. And comparison of the maximum storm surge height for all five events shows simulated data for both the data sets were close to the reported data and the difference was well within the margin of error. The results indicate MRI model as a useful tool for storm surge forecasting The Dhaka University Journal of Earth and Environmental Sciences, Vol. 9(1), 2020, P 31-38